2005
DOI: 10.1148/radiol.2372041174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Review Design on Percentages of Missed Interval Breast Cancers: Retrospective Study of Interval Cancers in a Population-based Screening Program

Abstract: The percentage of interval cancers classified as missed ranged from 1.3% to 35.9% according to review design. To encourage learning, a review protocol should include both blinded and informed designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 20 publications
4
48
0
Order By: Relevance
“…In particular, we used the clinically generated study reports in this study, while in our prior study we used retrospective review of the MR imaging acquisitions. While the current study used only cases interpreted by MR imaging experts, the retrospective review of the images, which also employed expert MR imaging readers, may be expected to increase the sensitivity for tumors ( 36,37 ), and yet we found that in our earlier study we achieved a lower sensitivity for smaller HCC. We also chose to exclude from statistical analysis nonnodule forming microscopic foci of malignancy that were incidentally detected at pathologic examination (three foci, all Յ 4 mm).…”
Section: Gastrointestinal Imaging: Mr Detection Of Hepatocellular Carmentioning
confidence: 72%
“…In particular, we used the clinically generated study reports in this study, while in our prior study we used retrospective review of the MR imaging acquisitions. While the current study used only cases interpreted by MR imaging experts, the retrospective review of the images, which also employed expert MR imaging readers, may be expected to increase the sensitivity for tumors ( 36,37 ), and yet we found that in our earlier study we achieved a lower sensitivity for smaller HCC. We also chose to exclude from statistical analysis nonnodule forming microscopic foci of malignancy that were incidentally detected at pathologic examination (three foci, all Յ 4 mm).…”
Section: Gastrointestinal Imaging: Mr Detection Of Hepatocellular Carmentioning
confidence: 72%
“…The increased rate of DCIS after implementation of screening programs may be due to better diagnostic equipments, and detection of non-symptomatic tumors. The somewhat high interval cancers in the NBCSP have been evaluated and discussed in previous papers [25,26], and the elevated rate in the second part of the interval may be explained by the definition, the use of the background incidence from an earlier time period without adjusting for temporal increases as discussed above, a somewhat low screen detection rate, and the possibility of opportunistic screening in the interval between two screening sessions in the NBCSP. Interval cancers reduce the effectiveness of mammography screening programs [3,7].…”
Section: Discussionmentioning
confidence: 96%
“…false negative) were more frequently lobular tumors and were larger than true interval cancers [148]. Tumor characteristics were similar for cancers detected in the first and second year following screening [144]. The prognosis for women with interval cancer was similar to the prognosis for women with breast cancer detected before screening implementation [147].…”
Section: Discussionmentioning
confidence: 71%
“…The rate of interval cancer (invasive and DCIS combined) following the prevalence screening round in the pilot counties was 1.95/1000 negative screens and the detection rate at screening was 6.72/1000 screens [146]. Following the subsequent three screening rounds, the rate of interval cancer (invasive and DCIS combined) in the pilot counties was 1.80 per 1000 screens and detection rate at screening 5.14 per 1000 screens [144]. Approximately 70-75% of the interval cancers were diagnosed in the second year following screening.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation